2013
DOI: 10.1002/ajpa.22243
|View full text |Cite
|
Sign up to set email alerts
|

Bony pelvic canal size and shape in relation to body proportionality in humans

Abstract: Obstetric selection acts on the female pelvic canal to accommodate the human neonate and contributes to pelvic sexual dimorphism. There is a complex relationship between selection for obstetric sufficiency and for overall body size in humans. The relationship between selective pressures may differ among populations of different body sizes and proportions, as pelvic canal dimensions vary among populations. Size and shape of the pelvic canal in relation to body size and shape were examined using nine skeletal sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
90
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 83 publications
8
90
1
1
Order By: Relevance
“…Kurki's (2013) findings on an archaeological collection were in line with those we report here. South African females displayed small pelvic inlets relative to a larger lower canal in anteroposterior diameters.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Kurki's (2013) findings on an archaeological collection were in line with those we report here. South African females displayed small pelvic inlets relative to a larger lower canal in anteroposterior diameters.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Kurki (2013) relates population specific variations in the pelvic canal to genetic reasons. Kurki's (2013) findings on an archaeological collection were in line with those we report here.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary theory would suggest that because 'selection intensity and phenotypic variability are inversely related' ( [143], p. 59), there should be sexual dimorphism in the variability of pelvic morphology, with variation in the size and shape of the female birth canal limited by obstetric demands. However, the nature and extent of sexual dimorphism in the modern pelvis are particularly complex, and a large number of studies have produced no clear indication that obstetric constraints produced between-sex differences in variability [3,18,138,139,[141][142][143]. To further complicate matters, work by Betti and co-workers [3,18,141] has suggested that among modern humans, neutral evolutionary processes reflecting demographic history have also been important in determining variation in pelvic form (see also [17]).…”
Section: The Evolution Of the Modern Human Pelvismentioning
confidence: 99%
“…The shape of the human pelvis is assumed to be a compromise solution. Human pelvises are shaped for upright walking, but at the same time, they must remain wide enough for giving birth to large-headed neonates (1,2,(9)(10)(11)(12). Upright walking evolved at least 4-5 million years ago and required major skeletal adjustments (9,13,14).…”
mentioning
confidence: 99%